PEMBERDAYAAN IBU-IBU PKK MELALUI PELATIHAN DAN PENDAMPINGAN PRODUKSI MINYAK ANGIN AROMATERAPI - Fransiska Leviana; Wiwin Herdwiani; Opstaria Saptarini (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2019)
The use of aromatherapy was very well known in the community. The best-selling and quickly accepted product was aromatherapy oil. The benefits of aromatherapy were not only for health, but also for calming the mind and relaxation. Empowerment of PKK as members of the community and still classified as productive workforce was very important to do, aiming to foster awareness and independence in doing business, while expanding employment to increase family income in an effort to achieve a happy and prosperous family. In relation to efforts to foster and develop the potential of families and regions, it can be done through various alternative activities, including training in making aromatherapy oil product. The purpose of this community service program was to empower mothers and women through training and assistance in aromatherapy oil production. The target of this activity was PKK RW 04 Mojosongo Village, Jebres District, Surakarta City. The output of this activity was improving the skills of the community to produce aromatherapy wind oil and motivating business opportunities for PKK mothers. The method used in this service was training and assistance in aromatherapy oil production.